Screening for Attention Deficit Hyperactivity Disorder at Elementary Schools in Baghdad City - Adnan, Husam; Rashak, Kareem (Iraqi National Journal of Nursing Specialties, 2020)
Objective(s): To determine the prevalence of ADHD among elementary school pupils; identify the association between pupil's level of ADHD and age, etc., and investigate the differences in pupils ADHD based on gender, and grade.Methodology: A descriptive study was conducted on elementary school pupils. The study started from the period of 16th of September 2019 to the 1st of October 2020. A cluster sample of 800 pupils was selected. The questionnaire was constructed and developed and include two parts: the first part includes the pupil's general information and the second part includes scale of ADHD prevalence.Results: The results of the present study indicated that 38(4.75%) of elementary school pupils probable had ADHD. There is a statistically high significant association between ADHD and parents' education level, parenting, and family income. There is a statistically high significant difference in pupils’ ADHD among their gender, and grade.Recommendations: The study recommended increase the screening of ADHD among school-age children and start the process of intervention as early as possible in order to help children with ADHD, especially in the first grade. Also, there is the need to intensively educate teachers on ADHD and how they can manage these pupils.